Can participatory budgeting mitigate government debt risk？—An empirical analysis using cross-national panel data - Yongpeng Li; Qianqian Zhang (PLoS ONE, 2025)
Objectives Participatory budgeting, serving as a complementary mechanism to traditional democratic practices, grants citizens direct involvement in the budgetary decision-making process, thereby embodying features of direct democracy. It has consequently gained recognition and promotion in numerous countries. However, scholarly opinion remains divided regarding the efficacy of participatory budgeting in mitigating government debt risks. This study seeks to address this ongoing academic debate by employing a cross-national panel data. Methods Utilizing a dataset of 664 samples from 83 countries between 2008 and 2023, sourced from the International Budget Partnership (IBP), this study combines survey data on public participatory budgeting opportunities with government debt statistics from the International Monetary Fund (IMF). Fixed-effects and mediating effect models are employed to empirically examine the relationship between public budget participation and government debt risk. Results Our analysis indicates that, on average, government debt risk is markedly lower in cases of participatory budgeting, a finding that is significant at the 1% level. This finding remains robust after replacing the explained variable to address robustness concerns and employing instrumental variables to mitigate endogeneity issues. Mediation analysis further indicates that the quality of explicit debt disclosure serves a significant mediating role, whereas contingent liabilities do not exhibit a mediating effect. Additionally, the mitigating effect of participatory budgeting on government debt risk is more pronounced in countries adopting accrual-based government accounting compared to those using cash-based accounting.